Displaced supracondylar femoral fractures: Clinical and radiographic outcomes in children aged 4–10 years treated with Kirschner wires and hip spica cast - Jing, Yanhui; Ning, Bo; Mo, Yueqiang; Wang, Dahui (Frontiers in Pediatrics, 2023)
Background: Supracondylar femoral fractures (SFFs) are uncommon in children but may result in various deformities. Although many approaches have been used to manage these fractures, there is no approved standard yet. Objectives: To evaluate the clinical and radiographic outcomes of displaced SFFs treated with Kirschner wires (K-wires) and hip spica cast in children aged 4–10 years Methods: We retrospectively reviewed 22 displaced SFFs (mean age, 6.7 years; range, 4–10 years) in patients who underwent surgical treatment with K-wires and hip spica cast. The patients were followed up radiographically and clinically on a regular basis from January 2014 to February 2019. Postoperative healing and functional outcomes were elevated according to radiographic and clinical measures. Results: Fifteen boys and seven girls were included in this study. All patients except two (91%) underwent close reduction and stabilization of the fractures. The mean follow-up duration was 4 years (range, 2–5 years). All fractures showed clinical and radiological evidence of union at 4–8 weeks after surgery. All the patients were pain–free at the last follow-up and returned to full normal activities. The mean Knee Society Score was 95.41 at the final follow-up. According to the radiologic criteria,18/22 patients (81.8%) obtained excellent results, 3/22 (13.6%) had good results, 1/22 (4.5%) had fair results, and none had poor results. Conclusion: Satisfactory clinical and radiological results can be expected in children aged 4–10 years treated with K-wires and hip spica casts.